Effect of adhesive system type and tooth region on the bond strength to dentin - de Melo, Renata Marques [UNESP]; Galhano, Graziela A. P. [UNESP]; Barbosa, Silvia Helena [UNESP]; Valandro, Luiz Felipe; Pavanelli, Carlos Augusto [UNESP]; Bottino, Marco Antonio [UNESP] (Quintessence Publishing Co Inc, 2008)
Purpose: This study evaluated the bond strength of two etch-and-rinse adhesive systems (two- and three-step) and a self-etching system to Coronal and root canal dentin.Materials and Methods: The root canals of 30 human incisors and canines were instrumented and prepared with burs. The posts used for luting were duplicated with dual resin cement (Duo-link) inside Aestheti Plus #2 molds. Thus, three groups were formed (n = 10) according to the adhesive system employed: All-Bond 2 (TE3) + resin cement post (rcp) + Duo-link (DI); One-Step Plus (TE2) + rcp + DI; Tyrian/One-Step Plus (SE) + rcp + DI. Afterwards, 8 transverse sections (1.5 mm) were cut from 4 mm above the CEJ up to 4 mm short of the root canal apex, comprising coronal and root canal dentin. The sections were submitted to push-out testing in a universal testing machine EMIC (1 mm/min). Bond strength data were analyzed with two-way repeated measures ANOVA and Tukey's test (p < 0.05).Results: The relationship between the adhesives was not the same in the different regions (p < 0.05). Comparison of the means achieved with the adhesives in each region (Tukey; p < 0.05) revealed that TE3 (mean standard deviation: 5.22 +/- 1.70) was higher than TE2 (2.60 +/- 1.74) and SE (1.68 +/- 1.85).Conclusion: Under the experimental conditions, better bonding to dentin was achieved using the three-step etch-and-rinse system, especially in the coronal region. Therefore, the traditional etch-and-rinse three-step adhesive system seems to be the best choice for teeth needing adhesive endodontic restorations.
Keywords: bond strength; push-out test; coronal dentin; root canal dentin; dental adhesives